Physical, biochemical, and microbial controls on amino sugar accumulation in soils under long-term cover cropping and no-tillage farming. (August 2019) - Li, Lidong; Wilson, Candace B.; He, Hongbo; Zhang, Xudong; Zhou, Feng; Schaeffer, Sean M.
Abstract: Understanding the processes controlling amino sugar accumulation in soil is essential for predicting the contribution of microbial residues to soil organic matter (SOM). The accumulation of amino sugars in soil is affected by multiple factors. Seldom are those factors examined together. We measured amino sugar concentration, extracellular enzyme activity, microbial respiration rate, and soil aggregate composition in an agricultural soil under 33-years of conservation management. The accumulation patterns of different amino sugars under the effects of no-tillage farming and cover cropping were compared and contrasted. The relative importance of physical, biochemical, and microbial controls of amino sugar accumulation was quantified using structural equation modelling. Our results show that although different types of amino sugars exhibited similar accumulation patterns in soil, their stabilization mechanisms might vary as demonstrated by structural equation models. The structural equation models indicate that macroaggregates had the largest total effect (0.59, P < 0.05) on muramic acid, and microbial respiration rate and wheat cover crops had large total effects (0.50 and −0.48 respectively, P < 0.05) on glucosamine. These results suggest that physical protection of soil aggregates played a critical role in muramic acid stabilization in soil, while microbial activity and nutrient condition were more critical for glucosamine. We also observed 24%–35% of decreases in soil amino sugars when nitrogen (N) was scarce and carbon (C) was excessive, concomitant with increases of extracellular enzyme activities. These results may support the theoretical model of microbial N mining. Structural equation model indicates that β-N-acetylglucosaminidase (NAG) had a negative effect on total amino sugars (−0.41, P < 0.05) and soil N had a negative effect on NAG (−0.27, P < 0.05). These results suggest that amino sugars can be decomposed by NAG as an alternative N source for microbes when readily available N was low. Leucine aminopeptidase (LAP) had a positive total effect on total amino sugars and a negative total effect on NAG (0.26 and −0.26 respectively, P < 0.05). This indicates that decomposition of amino acids by LAP may be a preferred strategy prior to decomposition of amino sugars by NAG to meet N requisition. Highlights: No-tillage and N-fixing cover crops promote the accumulation of microbial residues. Muramic acid is mainly protected by macroaggregates. Accumulation of glucosamine in soil is controlled by microbial activity and nutrient availability. The bioavailability and stability of soil amino sugars can be nutrient-dependent.